2015
DOI: 10.1002/hed.23967
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated radiotherapy for early‐stage glottic cancer

Abstract: IMRT is as efficient as conventional radiotherapy in terms of disease control and overall survival. It has the potential to reduce toxicity as compared to conventional radiotherapy. © 2015 Wiley Periodicals, Inc. Head Neck 38: E179-E184, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The use of 3DCRT with parallel opposing fields has been the standard technique. IMRT is as efficient as 3DCRT in terms of disease control and overall survival [11] and is a widely favored technique in the treatment of head and neck cancer [12][13][14][15]. The 5-year local control rate was reported as 94% in T1a and 93% in T1b glottic squamous cell carcinoma, respectively [4,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of 3DCRT with parallel opposing fields has been the standard technique. IMRT is as efficient as 3DCRT in terms of disease control and overall survival [11] and is a widely favored technique in the treatment of head and neck cancer [12][13][14][15]. The 5-year local control rate was reported as 94% in T1a and 93% in T1b glottic squamous cell carcinoma, respectively [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Zumsteg et al [7] retrospectively analyzed 330 T1 and T2 patients and reported a 3-year local control rate of 88% with carotid-sparing IMRT and 89% with conventional RT, with no statistically significant differences. Berwouts et al [11] reported a study that compared 40 patients with T1-T2 disease treated with IMRT without dose constraint for the carotid artery and 81 patients treated with conventional 3DCRT. There was no significant difference in 5-year local control between the groups, and significantly less skin toxicity in the IMRT group.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other reports, which have not identified improvement in voice outcomes. Alternatively, IMRT planning has been shown to reduce the severity of acute radiation dermatitis and to spare dose to the carotid vessels (34, 35). Intriguingly, preliminary reports from a prospective study examining the feasibility of IMRT-based single vocal cord irradiation for T1a glottic tumors has demonstrated promising 2-year local control rates and a modest, transient decline in voice quality by voice handicap index.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that techniques using RT for uniform dose distribution to the target volume, such as intensity-modulated RT (IMRT), may improve the local control rate for early-stage glottic carcinoma treated with definitive RT. Only a limited number of studies have evaluated the treatment outcomes of IMRT for early-stage squamous cell carcinoma of the glottis (27,28). In these studies, the local control rate did not differ significantly between patients treated with IMRT and those treated with RT.…”
Section: Discussionmentioning
confidence: 99%